Capital Budgeting Analysis in Assess the Feasibility of Vaname Shrimp Cultivation Investment - Gusni Gusni; Siti Komariah; Lia Amaliawiati (Universitas Batanghari Jambi, 2023)
Vannamei shrimp cultivation business is one type of business that has the potential to be profitable considering the high level of demand every year and of course also requires a fairly large investment. A true investment is an investment made through a feasibility analysis process to determine whether the business activity to be carried out is profitable or harmful. Good investment decisions will result in good business even though the financial decisions taken are not good, on the contrary the wrong investment decisions will be the wrong decisions that will be detrimental even with the best financial policies. The purpose of this study is to determine the feasibility of investment in vaname shrimp farming located in South Lampung Regency, both traditionally, semi-intensively and intensively. This study uses primary data and secondary data. Primary data is obtained from the results of field surveys, while secondary data is obtained from related agencies. The analytical method used in this research is the capital budgeting technique with the approach of NPV, IRR, Gross B/C, and PI. The results of the study using the four methods of capital budgeting above show that investment activities in vaname shrimp farming, both traditional, semi-intensive and intensive, are feasible. The most feasible and profitable method of vaname shrimp cultivation is intensive, which of course also requires the largest investment.